Emergence of enterovirus D68 in a Norwegian paediatric population 2012-2022 - Landaas, Elisabeth Toverud; Klundby, Ingvild; Knudsen, Per Kristian; Kran, Anne-Marte Bakken; Dudman, Susanne; Lind, Andreas; Holberg-Petersen, Mona (Frontiers in Virology, 2024)
Background: Enterovirus D68 (EV-D68) primarily causes respiratory infection, occasionally manifesting with neurological symptoms. Outbreak reports have been published from various countries including Norway, but a longitudinal study on EV-D68 prevalence in Northern Europe is lacking. Methods: Respiratory samples from children ≤14 years received at Oslo University Hospital in the years 2012-2022 were examined for EV-D68. Samples from 2012-2015 were retrospectively screened using a semi-specific RT-PCR, with positive samples confirmed by an EV-D68 specific RT-PCR. Samples from 2016-2022 underwent routine diagnostics with the EV-D68 specific RT-PCR. Results: Among the 22,911 samples tested, EV-D68 was detected in 338 samples (324 patients). Most EV-D68 cases occurred in August to December. The highest detection rate was recorded in 2014, 2016 and 2022 (6.0%, 7.8% and 6.6% of samples from August-December). Lower frequencies were observed in 2018 and 2019 (1.0% and 2.4%), and in the years before the 2014 outbreak (2012: 1.3%, 2013: 0.8%). Few cases were identified in 2020-2021. Children aged 0-1 years accounted for 40%, and 0-4 years for 78%, of the EV-D68 positive patients. Most of the patients with EV-D68 (83%) were hospitalised. Discussion: Also in Norway, EV-D68 has caused outbreaks with significant disease burden, especially among the youngest children. The detection rate varies, with a trend towards biennial outbreaks, except for low numbers in 2018 and during the COVID-19 restrictions (2020-2021). Due to its potential for severe respiratory illness and significant neurological complications, conducting EV-D68 testing is essential both for diagnosing clinically suspected cases, and for monitoring the disease burden.